The Use of Video in Teaching Writing Procedure Text (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
This study attempts to answer three research questionsdealing with the use of video inteachingwriting procedure text. The questions are; 1) How is the use of video in teaching writing procedure text? , 2) How are the students’ writing after the use of video?, and 3) How are the students’ responses towards the use of video in teaching writing procedure text?.Since this study was descriptive qualitative study, the writer would describe and analyze the existing phenomena during the study. Furthermore, there were three kinds of instruments used in this study. They were observation checklist, students’ writing, and questionnaire.Based on the findings, the writer noticed that the use of video mostly had the same activities although it was done in three meetings. The notes were about the analysis of teacher’s activity, students’ activity, teaching and learning process, material, and media used. In addition, the use of video helped students to create procedure text based on its generic structures and language features. Meanwhile, the result of students’ responses showed that the students were mostly interested in video viewing and agreed that video was helpful in getting the ideas to write.